Value Chain and Competitiveness of Plantain in Southwestern Nigeria (2015)
Nigeria ranks fifth in world plantain production but has low export volume. The low export may be a result of activities along its value chain. However there is little information on the number of employment generated, comparative advantage, competitiveness and effects of policies on plantain. Therefore, the competitiveness of plantain along the value chain in southwestern Nigeria was investigated. A three stage sampling procedure was used. The ten high plantain producing Local Government Areas (LGA) were selected in southwestern Nigeria. In each LG, two plantain producing villages were randomly selected. Producers (260) and 100 processors were randomly selected based on probability proportionate to size of villages. One hundred and forty four marketers were also randomly selected in the geopolitical zone. Structured questionnaire was used to collect information on number of job generated, cropping systems, quantity of input, output and their prices on each stage (production, farm gate and market arena assembling, processing, in-situ and transit wholesaling and retailing) of the chain. Secondary data on port charges, import/export tariffs and exchange rates were sourced from Nigeria Port Authority and trade statistics. Data were analysed using descriptive statistics, policy analysis matrix, sensitivity and partial equilibrium analyses. Major stages in plantain value chain were input supply, production, assembling, processing, wholesaling and retailing. Employment generated was 314 people/tonne with highest number (33.8%) in processing stages. Plantain/cocoa represented the highest cropping system (37.7%) while plantain/cassava (13.1%) was the least. Highest private and social profits of ₦514,547/ha and ₦1,593,611/ha were obtained in plantain/cocoyam at production stage respectively. Private Cost Ratio (PCR) ranged from 0.27 to 0.36 while Social Cost Benefit (SCB) ratio was 0.21 to 0.26. Profitability Coefficient (PC) of 0.20 to 0.32, Effective Protection Coefficient (EPC) of 0.26 to 0.37, and Subsidy Ratio to Producers (SRP) of -0.52 to - 0.62 were recorded at market price at the production stage. Plantain chips and flour had private profit of ₦426,339 and ₦408,701 and social profit of ₦764,793 and ₦561,969/tonne respectively at the processing stage. Both plantain chips and flour respectively had PCR of 0.15 and 0.11 and SCB of 0.34 and 0.33. Profitability coefficient of 0.73 and 0.56, EPC of 0.60 and 0.76 and SRP of -0.18 and -0.29 were obtained for plantain flour and chips respectively. Wholesalers had highest private profit of ₦36,800/tonne while farm gate assemblers had highest social profit of ₦137,812/tone at the marketing stage. The PC of 0.11 to 0.39, EPC of 0.12 to 0.41 and SRP of -0.24 to - 0.66 indicated lack of protection at the marketing stage. Aggregated value chain of the cropping systems had PCR of 0.18 to 0.35 and SCB of 0.30 to 0.37. Private profit of the producers respectively increased by 24.5% and 49.3% with 20.0% and 40.0% increase in yield levels. Net social loss in production was ₦6,552/tonne while consumers gained ₦28,295/tonne in the chain. Plantain/cocoyam production system had the highest private and social profits indicating that the system was profitable to participants and the southwestern economy.